Utilization of Tabut Local Wisdom in Social Studies Learning: Study of the Views and Strategies of Junior High School Teachers in Bengkulu City - Irwan Satria; Salamah Salamah; Harapandi Dahri (Indonesian Journal of Social Science Education (IJSSE), 2024)
Tabut is one of the traditions with a long socio-historical origin in Bengkulu, the implementation of Tabut continues to be carried out regularly every year (1-10 Muharam). In Bengkulu, the Tabut tradition is one of local wisdom characterized by moral values, especially religion and social values. From the educational perspective, specifically social studies education, Tabut’s local wisdom is very relevant to learning. This study aimed to 1) analyze the teacher's view of the integration of the value of Tabut local wisdom in social studies learning; 2) describe and analyze the social studies teachers' approaches and strategies in utilizing the value of Tabut local wisdom in social studies learning at junior high schools. This study was a descriptive qualitative research analysis. The object of the study was social studies learning in junior high schools in Bengkulu City. Data were elicited using interviews, questionnaires, and document analysis and literature study. Data analysis was carried out using an interactive model of Milles & Huberman. Based on the research, the results obtained are: 1) the use of local wisdom of Tabut in social studies learning at Junior High School in Bengkulu City is carried out with three main orientations, namely the cultivation of character values, the introduction of local Bengkulu culture and the use of local history and culture to enrich the national historical material. ; 2) the use of local wisdom of Tabut in social studies learning in junior high schools in Bengkulu City is carried out with an integrated approach to subjects, especially in the seventh grade (BC. 3.2 and BC. 3.4). As for the implementation of Tabut local wisdom in social studies learning, social studies teachers at SMP in Bengkulu City used two main strategies (models), namely Value Analysis and Value Clarification Techniques. Based on the results of research, it can be concluded that social studies teachers in Bengkulu City have positive views and have already utilized the Tabut local wisdom in social studies learning at Junior High School. However, the utilization has not well organized yet.